K-connectivity in shadowing wireless multi-hop networks - Zhang, Lili (2011)
In this paper, we study the network performance of a wireless multi-hop network in terms of the successful link probability and k-connectivity probability by taking into account shadowing. We provide the closed-form analytic results of the successful link probability, and henceforth k-connectivity, in the context of shadowing multi-hop networks. Given a certain number of nodes spatially distributed according to a Poisson point process, we examine the critical density to keep the probability that a node is k-connected close to 1. The impacts of the shadowing on the k-connectivity are illustrated and discussed. The results can be practically used for the design of a wireless multi-hop network.